1984
DOI: 10.1172/jci111424
|View full text |Cite
|
Sign up to set email alerts
|

Plasma growth hormone responses to constant infusions of human pancreatic growth hormone releasing factor. Intermittent secretion or response attenuation.

Abstract: As bstract. Administration of human pancreatic tumor growth hormone (GH) releasing factor ) as a single injection to normal human subjects stimulates the secretion of GH in a dose-responsive manner. In the present studies, hpGRF(1-40) was infused in a graded stepwise manner over a 6-h period in order to determine whether the GH secretory response would be sustained. Normal adult males received four consecutive 90-min infusions of hpGRF(1-40) at doses of 1, 3.3, 10, and 33 ng/kg per min, preceded and followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

1985
1985
1989
1989

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 30 publications
3
28
1
Order By: Relevance
“…Although the immunoreactive GRF levels did vary, they only accounted for 6% of the variation in GH secretion. In addition, the minimum levels observed (5 ng/ml) were 10-20-fold greater than the minimum levels we have observed that stimulate GH secretion in normal subjects (i.e., 300 pg/ml) (4). We calculated that this tumor secretes -4 mg of GRF per day, and thus this patient was exposed to the equivalent of a continuous infusion of GRF at a dose in excess of 28 ng/kg per min.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although the immunoreactive GRF levels did vary, they only accounted for 6% of the variation in GH secretion. In addition, the minimum levels observed (5 ng/ml) were 10-20-fold greater than the minimum levels we have observed that stimulate GH secretion in normal subjects (i.e., 300 pg/ml) (4). We calculated that this tumor secretes -4 mg of GRF per day, and thus this patient was exposed to the equivalent of a continuous infusion of GRF at a dose in excess of 28 ng/kg per min.…”
Section: Discussionmentioning
confidence: 84%
“…During infusions of incremental doses of hGRF-40, 1, 3.3, 10, and 33 ng/kg per min, each for 90 min, there appears to be a dose-related increase of GH secretion during the l-10-ng/kg per min infusions. During the 33-ng/kg per min dose, the effect wanes (4). However, there is great variability in the magnitude and timing of the GH responses among subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of GHRH at a constant rate in normal adults produces a persistent effect on GH secretion that is characterized by enhanced pulsatile secretion and an elevation of baseline GH secretion (10,26). These effects can be observed with infusions as short as a few hours and they persist for as long as 2 wk (27).…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure peripheral somatostatin in this study as we were unable to demonstrate a change in somatostatin concentrations (unpublished data) during previous dose-response investigations with GRF-44-NH2. Other investigators have reported no change in somatostatin concentration following intravenous bolus administration of (32) and no change in thyroid-stimulating hormone or thyrotropin-releasing factor-induced thyroid-stimulating hormone levels during continuous intravenous infusion of GRF-40 (33).…”
Section: In Vivomentioning
confidence: 95%